(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Businesses in the modern day have to contend with a lot of rivals, so they always have to think of new methods to set themselves apart from the competition and show that they are the best in their field. Consumers now have different expectations of the businesses they patronize. They want businesses to care about their communities as much as their customers. To show that they are a "socially responsible company," they are starting to employ cause-related marketing strategies. The term "Cause-Related Marketing" (CRM) refers to the various ways in which companies help out nonprofits and good causes by forming relationships that involve monetary donations and additional assistance gained through consumers, suppliers, or staff. In addition to boosting brand awareness, this method of advertising may also help improve people’s lives. It’s a strategy for achieving business goals while also helping solve pressing social concerns by directing capital and other resources toward such causes. To understand the view on purchase of product related to a social cause and to identify the determinants of CrM respondents’ priorities. The study has been conducted in Chennai city during the month of March 2022. Total sample respondents from the study area is 150 who have been selected using the convenient sampling method. To rank the type of cause related to CrM, Garrett ranking method and to measure perceptions on cause related marketing, the Likert’s Scale have been used.